Targeting TRIM5α in HIV Cure Strategies for the CRISPR-Cas9 Era - Weatherley, Daryl Anne Victoria; Boswell, Michael Terence; Rowland-Jones, Sarah L. (Frontiers in Immunology, 2017)
In the past decade, studies of innate immune activity against HIV-1 and other retroviruses have revealed a powerful array of host factors that can attack the virus at various stages of its life cycle in human and primate cells, raising the prospect that these anti-viral factors could be manipulated in immunotherapeutic strategies for HIV infection. This has not proved straightforward: whilst HIV accessory genes encode proteins that subvert or destroy many of these restriction factors, others, such as human TRIM5α show limited potency against HIV-1. However, HIV-1 is much more susceptible to simian versions of TRIM5α: could this information be translated into the development of an effective gene therapy for HIV infection? Reigniting research into the restriction factor TRIM5α in the era of superior gene editing technology such as CRISPR-Cas9 presents an exciting opportunity to revisit this prospect.